2022
DOI: 10.1177/09544062221101737
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent bearing fault diagnosis based on hybrid signal processing and Henry gas solubility optimization

Abstract: Bearing is regarded as one of the core elements in rotating machines and its fault diagnosis is essential for better reliability and availability of the rotating machines. This paper puts forward an intelligent vibration signal-based fault diagnosis approach for bearing faults identification at an early stage, irrespective of speed conditions. The proposed methodology comprises of a frequency shift-based hybrid signal processing technique that involves a combination of Hilbert Transform (HT) and Discrete Wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Accordingly, best parameters for each algorithm are used for solving the IKM of a three-section CR during tracking a spiral-like trajectory ( X = 8 t sin ( t / 2 ) , Y = 8 t cos ( t / 2 ) , 650 10 t ) ( t = 0 : 0 . 25 : 30 ) . The used codes to test the previously mentioned algorithm is inspired from HGSO, 3841 GA, 42 ABC, 43 and TLBO. 44,45…”
Section: Comparison Of Pso With Four Meta-heuristic Approaches In Ter...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, best parameters for each algorithm are used for solving the IKM of a three-section CR during tracking a spiral-like trajectory ( X = 8 t sin ( t / 2 ) , Y = 8 t cos ( t / 2 ) , 650 10 t ) ( t = 0 : 0 . 25 : 30 ) . The used codes to test the previously mentioned algorithm is inspired from HGSO, 3841 GA, 42 ABC, 43 and TLBO. 44,45…”
Section: Comparison Of Pso With Four Meta-heuristic Approaches In Ter...mentioning
confidence: 99%
“…Accordingly, best parameters for each algorithm are used for solving the IKM of a threesection CR during tracking a spiral-like trajectory (X =8t sin (t=2), Y = 8t cos (t=2), 650 À 10t) (t = 0 : 0:25 : 30). The used codes to test the previously mentioned algorithm is inspired from HGSO, [38][39][40][41] GA, 42 ABC, 43 and TLBO. 44,45 Comparatively speaking, the adopted meta-heuristic approaches for solving the IKM of a three-section CR are reliably accurate since the maximum error is less than 1 3 10 À5 mm (see Table 5 and Figure 14).…”
Section: Comparison Of Pso With Four Metaheuristic Approaches In Term...mentioning
confidence: 99%
“…Finally, the features are classified and learned. Commonly used traditional machine learning classification methods include K-nearest neighbors [16], support vector machines (SVMs) [17], and artificial neural networks [18], among others. The aforementioned methods excessively depend on expert knowledge and possess a shallow network structure, thereby impeding the extraction of profound feature information and failing to fulfill the present-day demands for extensive integration and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The schemes of time-frequency combined with neural networks have been maturely applied in the field of mechanical fault diagnosis [18,19]. However, it can be observed that the following challenges still exist in the above-mentioned methods.…”
Section: Introductionmentioning
confidence: 99%